Housing Wealth and Labor Supply of Elderly Workers: Evidence from China - Feng, Ziyi (Tufts University Tisch Library, 2025)
Thesis (M.S.)--Tufts University, 2025.; Submitted to the Dept. of Economics.; Advisor: Yannis Ioannides.; Committee: Jeffrey Zabel.; Keyword: Economics.